"Ploughing the land five times": Opium and agrarian change in the ceasefire landscapes of south‐western Shan State, Myanmar. (2nd September 2021) - Meehan, Patrick
Abstract: This paper explores the relationship between the illicit opium economy and processes of agrarian change in south‐western Shan State, Myanmar. This is a region where opium production has risen significantly since the 1990s despite the declining territorial control of insurgent groups long blamed for the country's illegal drug economy and alongside the deepening integration of the region's agriculture sector into national and global markets. This paper reveals how illicit opium cultivation has offered distressed smallholders a way to mitigate the worsening livelihood insecurities that have accompanied the commercialization of smallholder agriculture. Yet at the same time, opium cultivation has locked farmers into a set of highly unequal social relations that has enabled militias, businesspeople with ties to local (armed) authorities, moneylenders, and agricultural brokers to accumulate capital through their control over rural markets and credit systems while leaving poppy cultivators with little more than the means to reproduce their livelihoods. This paper thus shows how opium cultivation has enabled farmers to respond to worsening precarity by sustaining smallholder farming despite the worsening "reproduction squeeze" facing many households, although the opium economy has simultaneously played an instrumental role in reinforcing and deepening agrarian class relations.